PENGARUH IMPLEMENTASI KEBIJAKAN TUNJANGAN FUNGSIONAL BIDAN TERHADAP KINERJA BIDAN KABUPATEN MINAHASA SELATAN - MASINAMBOW, RAYMOND; Rompas, Welson Yappi; Tulusan, Femmy (Sam Ratulangi University, 2015)
ABSTRACT: Influence policy implementation midwife functional benefits to employee performance / midwife in South Minahasa district is intended to improve the quality of health services and prosperity the employees in this case the midwife.This research uses quantitative methods to do sampling for three (3) health centers and one (1) Department of Health Amurang South Minahasa District. Samples taken are all employees of the midwife in 3 health centers and 1 Amurang Health Service who are 40 respondents. Collecting data in statistical analysis using simple linear regression and correlation analysis of simple or product moment correlation.Based on data analysis showed: (1) the regression coefficient influence policy implementation midwife functional benefits to employee performance / midwife is 0.826 scale. (2) to determine the influence of the implementation of functional benefits midwife variable (X) on the performance of employees / midwife (Y), then applied to the calculation of determination by way mengkwadratkan correlation coefficient (r²). The calculation result of determination indicates that the effect of the implementation of the functional benefits of midwives to employee performance obtained by r² = (0.789) ² = 0.623 or 62.3%.Based on these results it can be concluded that the functional benefits of policy implementation midwife positive effect on employee performance or midwife in South Minahasa regency.Keywords: Functional Benefits Policy Implementation Effect on Performance Midwife